Analisa Program Cakupan Tuberklosis terhadap Penanggulangan Penyakit Menular pada Kasus Tuberklosis di Dinas Kesehatan Kabupaten Kerinci Tahun 2025 - Deasy Kristian Deasy Kristian; Dewi Riastawaty; Subang Aini Nasution (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Abstract. Tuberculosis is a public health problem that affects one third of the world's population. Tuberculosis is included in the 8 infectious diseases and causes the most deaths. The general objective of this research is to carry out an analysis of the tuberculosis coverage program for the control of infectious diseases in tuberculosis cases at the Kerinci District Health Service. This type of research is quantitative research using evaluative research through a cross-sectional approach, a research in which data collection is carried out only once at a time based on facts that have occurred in the past. The aim is to analyze the tuberculosis coverage program for the control of infectious diseases in tuberculosis cases at the District Health Service. This research will be carried out at the Kerinci District Health Service, while the address of this research location is Sungai Pegeh, Kec. Siulak, Kerinci Regency, Jambi in September 2025. The research population consisted of all 250 tuberculosis sufferers who lived in the working environment of the Kerinci Regency Health Service. The research sample was all tuberculosis sufferers who lived or lived around the work environment of the Kerinci District Health Service, totaling 250 people. Sampling in this research used the total population technique (saturated sampling), meaning that the research sample was taken by making the entire population the sample in the research. The instruments in this research consisted of a questionnaire sheet and an observation sheet. The research questionnaire consists of a questionnaire about the tuberculosis coverage program and a questionnaire about the management of infectious diseases. The analysis carried out on the research results was through univariate and bivariate analysis with the help of a computer to process the research data. The results of the research explain that there is a significant influence between the tuberculosis coverage program on the control of infectious diseases with a value of p = 0.001 (< 0.05)